H3K9 methyltransferases and demethylases control lung tumor-propagating cells and lung cancer progression - S. P. Rowbotham (Nature Portfolio, 2018)
The effects of epigenetic regulators on different tumor cell populations can affect their potential as anticancer targets. In this study, the authors demonstrate that the histone methyltransferase G9a is a suppressor of lung tumor-propagating cells and tumor progression, acting through chromatin modification with MMP10 as one of its targets for metastasis regulation.